The Songs of the Minnesinger, Prince Wizlaw of Rügen - Garvey Seagrave, Barbara (UNC Studies in the Germanic Languages and Literatures, 1967)
This work originally published in 1967 was the first to treat Wizlaw in his three roles of composer, poet, and sovereign and to present his poetry in English. Thomas and Seagrave also include a bibliography, translations and music transcriptions of all his songs, and photographic reproductions of corresponding folios of the Jena manuscript.